Phylogeography of Drosophila buzzatii (Diptera, Drosophilidae): responses of the species to Quaternary climates in tropical and subtropical South America - MATEUS HENRIQUE SANTOS; DORA YOVANA BARRIOS-LEAL; MAURA HELENA MANFRIN (Anais da Academia Brasileira de Ciências, 2023)
Abstract Drosophila buzzatii (Diptera: Drosophilidae) is a fly that breeds exclusively on decaying tissues of cacti species widely distributed in tropical and subtropical areas of South America. This distribution includes biomes in distinct climatic regimes (e.g., seasonal rain forest, semi-arid scrubs, savannas, and grasslands), which at first glance could might give the false impression that the species is not sensitive to either climate or vegetation physiognomies. However, detection of historical demographic events within D. buzzatii reveal the interplay between climate and the population structure of the species as the Late Quaternary climate changes occurred. To understand this process, we performed a phylogeographic analysis based on sequences of the mitochondrial gene COI for 128 individuals from 43 localities. Our analyses combined coalescent methods, population genetics, and paleodistributions estimation methods. Our study reveals that the COI haplotype diversity is geographically structured, with a decreasing cline from north to south. The results suggest an ancient range expansion, dated from 610k to 550k years before present, in the northernmost region of the species distribution, the Caatinga vegetation. More recently, an intense gene flow and a population expansion were detected in the central and south portions of its distribution. The demographic events detected date back to the glacial periods of the Quaternary.